Sacral neuromodulation: an effective treatment for lower urinary tract symptoms in multiple sclerosis. Issue 3 (March 2016) - Puccini, Federica; Bhide, Alka; Elneil, Suzy; Digesu, G.
Abstract Introduction and hypothesis Most subjects with multiple sclerosis (MS) suffer from lower urinary tract symptoms (LUTS). Detrusor overactivity, detrusor hypocontractility and detrusor–sphincter dyssynergia are the most common bladder dysfunctions. Management is not straightforward due to the progressive course of the disease. Sacral neuromodulation (SNM) has received increasing attention among new effective treatments for bladder disorders associated with MS. The aim of this study was to review the published literature on the role of SNM in the treatment of LUTS in patients with MS. Methods A literature search was carried out up to December 2014, using relevant search terms in MEDLINE and EMBASE databases. The ClinicalTrials.gov and Controlled-trials.com online trial registries and the abstracts from international scientific meetings were searched for English-language studies containing relevant search terms. Relevant reviews and trials and prospective studies were analysed by two independent reviewers. Results Two prospective studies and four retrospective studies were included. Overall, MS patients represented small series (4 to 25 subjects). The longest follow-up was 7 years and the evaluation of the treatment outcomes was not homogeneous among the studies. The definition of objective cure was often unclear. The subjective cure rate was 45 %, patients' reported satisfaction was 85 % and all the results were stable over time. Conclusions SNM seems to be a safe and effective treatment for LUTS in MS patients. Further and larger studies as well as randomized controlled trials are needed to confirm its clinical role in patients with MS.